UMAH INFORMASI DIGITAL DALAM UPAYA LITERASI DIGITAL MASYARAKAT DI WALANTAKA - BANTEN - Nina Yuliana; Isti Nursih; Muhammad Jaiz (Universitas Sanata Dharma, 2021)
The service program aims to increase public knowledge about various kinds of digital media literacy information, especially related to job opportunities, schools, Islamic boarding schools, and scholarships as an effort to form and develop an education literate society and alleviate poverty. The specific targets are: (1) Basic use of computers to search for information and needs; (2) the use of subjective needs and abilities; and (3) a consultation room for the information obtained. The method used: (1). Socialization about “Umah Information” at Azzahra Reading Park; (2). Socialization material according to target. The results of the service show that the village community is very interested in the digitization program, because of the availability of computers (PCs and laptops) that cannot be owned and accessed. Browsing is the easiest thing, as a habit from HP. The understanding and use of word, ppt, excel, and others is low, of the 30 participants consisting of elementary, high school students, junior high school age students - high school students, mothers and fathers from various professions, only those who have a profession as formal workers such as teachers, who already know, and are able to operate, and adapt quickly during training.